COUPLING THERMAL TREATMENT AND MICROBIAL REDUCTIVE DECHLORINATION FOR THE ENHANCED REMEDIATION OF CHLORINATED ETHENES - Marcet, Tyler. (2018)
Abstract: The targeted, synergistic implementation of in situ thermal treatment (ISTT) with microbial reductive dechlorination (MRD) has potential to enhance biodegradation of tetrachloroethene (PCE), trichloroethene (TCE), and their chlorinated daughter products, while reducing remedial costs and cleanup time relative to conventional in situ remediation technologies. Growth rates and activity of reductively dechlorinating bacteria have been shown to increase during or following field-scale ISTT, but the causal mechanisms are poorly understood. Two of the most likely mechanisms were investigated: 1) increased availability of bioavailable substrates in the aqueous phase and 2) direct temperature stimulation of the microbial community. Through a series of laboratory-scale batch reactor and 1-D column studies, electron donors and fermentable precursors released from porous media during thermal treatment were identified, quantified, and evaluated for their ability to promote the complete microbial reductive dechlorination of PCE to non-toxic ethene. Column studies were also completed to elucidate the impacts of temperature on the growth and activity of a dechlorinating consortium under continuous flow conditions. Results indicate that compounds released from soil organic matter during thermal treatment can represent a substantial source of bioavailable reducing equivalents, capable of sustaining bacterial ethene formation even in the absence of an external electron donor source. Sustained ethene formation was also demonstrated at elevated temperatures previously believed to inactivate key reductively dechlorinating bacteria. Collectively, results reaffirm the argument for the coupled implementation of ISTT and microbial reductive dechlorination technologies, and underscore the potential to improve contaminant degradation rates.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Civil Engineering.; Advisors: Natalie Capiro, and Kurt Pennell.; Committee: Frank Loffler, and Ayse Asatekin.; Keyword: Environmental engineering.